Theoretical Analysis of the Role of Ethics in Decision-Making: A Philosophical Approach to the Values of Integrity and Public Service - Aan Warul Ulum (International Publisher, 2025)
This theoretical analysis explores the role of ethics in public decision-making, focusing on the values of integrity and public service. It examines how ethical frameworks specifically deontological ethics, virtue ethics, and care ethics inform and guide the conduct of public officials. The study highlights the challenges faced by public administrators in aligning moral obligations with political pressures and institutional constraints. Through a philosophical lens, the paper discusses the implications of ethical decision making on public trust and institutional legitimacy. The findings underscore the necessity for integrating ethical principles into public administration to foster accountability, transparency, and public confidence. The analysis concludes by emphasizing the importance of ethical education and institutional mechanisms in supporting ethical conduct among public officials.